Spletne zbirke na spletni strani Slovenskega etnografskega muzeja - Špiček, Miha (Knjižnica, 2012)
Are you interested in the night view of Ljubljana or in the view on the Ljubljana skyscraper in the 30-ies of the 20th century? What did Cerknica look like in tham time? What did a typical alpine house look like? What beds were used fifty years ago? Are you a sports fan interested in the training of Yugoslav athletic team in 1953? Is it true that Anton Codelli and his colleague Leo Poljanec set up the first wireless telegraph station for the company Telefunken in the West African German colony of Togo? What is a Palm Sunday bundle? Is a duel between a woman of Carinthia and carniola really painted on a wooden bee hive panel? What on earth is an object called "roš"? What chimneys were built on the roofs of the Artiže village? The answers to these unusual questions can be found on the SEM (Slovene Ethnographic Museum) website. The SEM documentation comprises numerous collections of photographs which are of interest to ethnologists as well as to the general public. To facilitate the access to them SEM bought the first scanner and started to scan individual photos in 1997. In 2007 SEM continued with systematic digitisation of the most frequently used collections of photos. In 2009 the activities were continued (partly in cooperation with external partners) and we joined the Athena EU project. In order to be promoted the entire collections were published on the SEM website and made accessible to a broad audience. The MINOK software enabling the creation of html catalogues was used. As static catalogues were unsuitable for inclusion on the website, a new application using dynamic html was designed to create the gallery view of museum objects and photos, photo slide show, keyword filter, geolocation filter, display of geolocation on a map, and to offer the possibility of advanced searching. The Galerist software was designet by an external partner. It enables html catalogue import, sorting and editing XML files; it is possible to add geolocation and to create specific collections etc. The Galerist web application was integrated to the SEM website which is built on the Drupal open source content management system (CMS). As the two search engines were not linked together, users had to make two separate searches which proved to be inconvenient. Many website visitors used the Drupal search engine instead of the Galerist. As the Drupal search engine is not convenient for simple searching, we decided to import the entire collection to the Drupal to facilitate the searching and to enable users to search the Galerist and the Drupal simultaneously. SEM collection were published on the website in 2010. They are divided into Collections of objects (e.g. photos of Palm Sunday bundles, the Kos collection, Folk instruments, Ploughs, Painted beehive panels, Headwear, Plastic carnival masks, Tally sticks, Blue-printing models, Superstition, Ploughing implements, the Milan Kovač collection and Horsehair sieves. They can be accessed at http://www.etno-muzej.si/sl/zbirke-predmetov) and Collections of photos (photos of 32 terrains shot by the teams under the guidance of dr. Boris Orel and other individual albums: Vekoslav Kramarič, Rado Kregar, Matija Murko, Slavko Smolej, Veno Pilon, Jernej Šušteršič, Press Office, Togo Album, Fran Vesel, Collection of old photos and Collection of Marko Račič´ sports photos. They can be accessed at: http://www.etno-muzej.si/sl/zbirke-fotografij). The web collection comprises 55 collections with more than 23,000 entries. On the basis of Web statistics and users´ feedback we can assume that our collections are of interest to the general public. The primary goal to promote our cultural heritage was attained as people are generally acquainted with our permanent exhibitions but less familiar with our collections. Digitisation was funded by the EU Athena project - our collections are accessible via the Europeana website. SEM web collections project has not been concluded yet and is being constantly upgraded.
Keywords: muzeji; Slovenski etnografski muzej; Ljubljana; muzejske zbirke; digitalne zbirke; spletne zbirke; digitization; digitalizacija